Sycetta papillata sp. nov. (Porifera, Calcarea): the first record of Sycetta to the Southwestern Atlantic Ocean - Mattedi, Alice; Cavalcanti, Fernanda F. (Zootaxa, 2024)
Sycetta is a poorly known genus of calcareous sponges, primarily distinguished by the presence of tubes (the choanocyte chambers) radially organized around the atrial cavity and completely separated from each other. These tubes, referred to as conical diverticula or more aptly as papillae, impart a distinctive appearance to the external morphology of the sponges. Herein, we present the description of Sycetta papillata sp. nov., based on the examination of specimens collected several decades ago in the state of Bahia, located in Northeastern Brazil. The presence of a single category of diactines and atrial region formed exclusively by tetractines makes this species unique within the genus. While some species of Sycetta have been documented in deep regions, exceeding depths of 200 meters, the distribution range of S. papillata sp. nov. spans from 0.5 to 25 meters in depth. A comparative table of Sycetta species is being provided.